Manfred Oskar Eitel Hennies – 85 (10.09.1938 – 18.10.2019) - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2024)
Co-organizer of the conference and long-term active participant (since the first international conference, 1996–2016) and Editor of publications-journal „Estonian Discussions on Economic Policy“ Professor emeritus (Applied University of Kiel, Germany) Dr Manfred Oskar Eitel Hennies – 85 years (10.09.1938 – 18.10.2019)